2013
DOI: 10.3402/gha.v6i0.21064
|View full text |Cite
|
Sign up to set email alerts
|

Use of anchoring vignettes to evaluate health reporting behavior amongst adults aged 50 years and above in Africa and Asia – testing assumptions

Abstract: BackgroundComparing self-rating health responses across individuals and cultures is misleading due to different reporting behaviors. Anchoring vignettes is a technique that allows identifying and adjusting self-rating responses for reporting heterogeneity (RH).ObjectiveThis article aims to test two crucial assumptions of vignette equivalence (VE) and response consistency (RC) that are required to be met before vignettes can be used to adjust self-rating responses for RH.DesignWe used self-ratings, vignettes, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…We also note that the validity of the anchoring vignette method hinges critically on the maintenance of both vignette equivalence and response consistency assumptions. A number of studies have investigated the plausibility of these assumptions; some have found positive supports [ 19 , 26 , 31 ], while others report possible violations [ 5 , 6 , 8 , 13 ]. In this study, there is always the possibility that these assumptions are violated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also note that the validity of the anchoring vignette method hinges critically on the maintenance of both vignette equivalence and response consistency assumptions. A number of studies have investigated the plausibility of these assumptions; some have found positive supports [ 19 , 26 , 31 ], while others report possible violations [ 5 , 6 , 8 , 13 ]. In this study, there is always the possibility that these assumptions are violated.…”
Section: Discussionmentioning
confidence: 99%
“…Anchoring vignette is a promising method that offers a direct way of handling interpersonal incomparability in self-report measure. Although methodologists have extended the original anchoring vignette method [ 19 ] to accommodate more complex situations [ 4 , 6 , 17 , 23 , 24 , 31 , 36 ], adequate attention should also be given to the fundamental matters of question wording [ 1 , 13 ] and ordering [ 7 , 14 ]. We believe that, given its cost-effectiveness and feasibility in large-scale surveys, SRH and anchoring vignette have the potential to play a greater role in public health research in now-decentralised Indonesia, where more than 500 local administrations must struggle with a scarcity of competent health workers [ 27 , 33 ] as well as with the high cost of collecting objective health measures.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work on related vignettes (covering mobility and cognition) suggests that although the psychometric performance of vignettes in WHO-SAGE is imperfect at predicting anchoring in absolute terms, the vignettes still provide information on how individuals order severity of conditions, particularly for self-care. 25 The vignettes covered: a person able to wash, bathe and dress himself slowly; a person housebound because of arthritis who cannot dress and needs help with washing; a person able to self-care except for occasional help with bathing and dressing when he has back pain; and a person requiring help with all care because of paralysis from the neck down. For each vignette, we asked a question on ability to self-care and a question on maintaining appearance, corresponding to questions asked on self-care and appearance within WHODAS-II.…”
Section: Methodsmentioning
confidence: 99%
“…Provided that two key identifying assumptions hold, namely response consistency (RC) and vignette equivalence (VE), these ratings can reveal what the response categories truly mean for respondents, and can therefore be used to identify and adjust for DIF. The approach has been used in a number of applications including political efficacy (King et al, 2004), job,income,life, and health satisfaction (Angelini, Cavapozzi, Corazzini, & Paccagnella, 2014;Bertoni, 2015;Crane, Rissel, Greaves, & Gebel, 2016;Kapteyn, Smith, & Van Soest, 2013;Kristensen & Johansson, 2008) and general and specific dimensions of health Dowd & Todd, 2011;Grol-Prokopczyk et al, 2011;Hirve et al, 2013;Molina, 2016;Peracchi & Rossetti, 2012).…”
mentioning
confidence: 99%